Development of Effective Learning Strategies to Improve Social-Emotional Skills in Early Childhood - Ishak Bagea; Abu Muna Almaududi Ausat; David Rindu Kurniawan; Kraugusteeliana Kraugusteeliana; Hizbul Khootimah Azzaakiyyah (Departement of Mathematics Education, 2023)
Early childhood education has a very important role in early child development. Education provided in early childhood must be comprehensive, covering various aspects such as social-emotional, cognitive, physical and language skills. However, social-emotional skills often do not get enough attention in early childhood learning. So, this research will discuss the development of effective learning strategies to improve social-emotional skills in early childhood. The focus of this study is primarily qualitative. Listening to and recording pertinent information is a data collection method that can then be used in data analysis steps like summarization and visualisation. Study ii came to the conclusion that developing effective learning strategies can improve social-emotional skills in early childhood. Some strategies that can be implemented and are potentially effective include implementing learning programmes based on children's needs and interests, using interactive and collaborative learning methods, and facilitating a safe, comfortable and supportive learning environment.